Figuracje oraz antropomorfizacje w pradziejach i starożytności - Bugaj, Ewa (Wydawnictwo Poznańskie, 2010)
The introduction into the issues discussed in the book 'Aesthetics in Archaeology' (no. 3) is entitled ‘Figuration and anthropomorphization in prehistory and antiquity’, as research perspectives presented here oscillate, on the one hand, around specific human-like artefacts, produced in various cultural circles, starting from the preserved oldest visual images until the present. On the other hand, the papers indicate that anthropomorphism is a much wider and capacious phenomenon, consisting in attributing human characteristics to inanimate world, or, wider, on projecting human qualities onto the whole surrounding reality or even on impossibility of recognizing the reality beyond the anthropomorphising ‘I’. It must be emphasised that reflections presented in the books are not limited to perceiving archaeology as a discipline interested only in the past studied by the prism of material remains, here preserved relicts of figural art. On the contrary, they make us realise that those remains (even so meaningful as works of art) are not identical with the culture of these past societies or with them. They constitute just a fragment of the then culture, which did not function autonomously but in connection with other domains, especially symbolic culture, which cannot be studied empirically. Taking under consideration the specificity of archaeological sources, we always have to refer to a theory as a means of mediation between their materiality, past socio-cultural reality, the present and the researcher.
Figuration and Anthropomorphization in Prehistory and Antiquity
Keywords: prehistoric art; ancient art; archaeological method and theory